Anti-aging effect of Lactobacillus plantarum HFY09-fermented soymilk on D-galactose-induced oxidative aging in mice through modulation of the Nrf2 signaling pathway. (March 2021) - Zhou, Xianrong; Sun, Hailan; Tan, Fang; Yi, Ruokun; Zhou, Chaolekang; Deng, Yuhan; Mu, Jianfei; Zhao, Xin
Graphical abstract: Highlights: Lactobacillus plantarum HFY09 shows good in vitro resistance. The soy isoflavones and peptides in fermented soymilk were significantly different from that of unfermented soymilk. Oral gavage of fermented soymilk could improve related physiological and biochemical indicators in serum, liver, spleen, skin and brain tissue of aging mice. The anti-aging mechanism of L. plantarum HFY09-fermented soymilk may be related to the activation of the Nrf2 signaling pathway. The results will provide theoretical basis and available strains for the development and utilization of value-added fermented soybmilk. Abstract: After soymilk fermented by L. plantarum HFY09, the bound soybean isoflavones content was reduced, but free soybean isoflavones and peptides increased. In vivo results show that L. plantarum HFY09-fermented soymilk increased the T-SOD, MDA, GSH-Px, GSH, CAT, and NO in the serum, liver, and brain tissues of mice. The aforementioned soymilk also increased the Col I and hyaluronic acid, and reduced the contents of Col III, H2 O2, and AGEs in the skin. L. plantarum HFY09-fermented soymilk upregulated Nrf2, HO-1, NOS1, NOS3, SOD1, SOD2, CAT, Nqol, Gclm expression in the liver and the spleen, reduced the NOS2 expression, and upregulated SOD1 SOD2, CAT, GSH-Px, TIMP1, and TIMP2 expression in skin, downregulated MMP3, and MMP9 expression. These results show that L. plantarum HFY09-fermented soymilk could effectively alleviate aging in D-galactose-induced aging mice, the mechanism may be related to the activation of Nrf2 signaling pathway by soy isoflavone aglycone and small molecule peptides.